PRODUCTION AND CHARACTERIZATION OF POLYHYDROXYBUTYRATE BY ENTEROBACTER SP. USING GELIDIUM SP. HYDROLYSATE AS A CARBON SOURCE - Gede Tirta Andini, Desak
Polyhydroxybutyrate (PHB) is a type of bioplastic with great potential as a substitute for conventional petrochemical-based plastics due to its biocompatible and biodegradable properties. This research aims to develop PHB production using Gelidium sp. hydrolysate as a carbon source through fermentation by Enterobacter sp. The hydrolysate was obtained through a process using dilute acidon Gelidium sp., which converts polysaccharides into monosaccharides that can beutilized by microorganisms. The fermentation process was controlled under variousconditions to optimize PHB production, including hydrolysate concentrations ranging from 5- 15% v/v in the PHB production medium. The produced PHB was comprehensively analyzed using various characterization methods. The characterization methods used were FTIR and XRD, DSC, and TGA/DTG. This study resulted in optimal hydrolysis conditions at a dilute acid concentration of 0.35 M with a sugar content of 498.30 ± 22.16 mg/ml. The optimum production conditions were then obtained at a hydrolysate concentration of 10%, with the amount of biomass and PHB being 21.8 ± 0.005 mg and 3.51 ± 0.75 mg, respectively. These results indicate that Enterobacter sp. can effectively utilize Gelidium sp. hydrolysate, producing PHB under optimal fermentation conditions. FTIR and XRD analysis confirmed that the synthesized PHB has a structure similar to standard PHB and possesses high crystallinity. DSC and TGA/DTG analyses showed that the synthesized PHB has good thermal stability, with significant massloss occurring at 91.7°C and 250- 300°C, respectively. These findings suggest thatGelidium sp. hydrolysate can be efficiently used as a carbon source for PHB production by Enterobacter sp., with polymer characteristics suitable for bioplasticapplications.